Hubungan Dukungan Sosial Teman Sebaya Dengan Tingkat Kesepian Pada Lansia Di Wilayah Kerja Puskesmas Payung Sekaki - Nengsih, Devi Kemalasari; Zulfitri, Reni; Annis Nauli, Fathra (Yayasan Jompa Research and Development, 2025)
Background: Peer social support is a factor in loneliness in the elderly. Purpose: This study aims to determine the relationship between peer social support and the level of loneliness in the elderly in the Payung Sekaki Health Center WorkingArea. Methods: This research uses a descriptive correlation design and a cross sectional approach. The research sample was 100 respondents taken using accidental sampling technique. The questionnaire used for loneliness is the UCLA(University of California Los Angeles) translation of the Loneliness Scale Version 3 and The Social Provision Scale (SPS) for measuring peer social support and has been tested as valid and reliable. Results: The research results showed that of the 100 respondents, 53% of the elderly were female, 81% were aged 60-74, 28% had an elementary school education, 55% had a married status and 75% had a type of work not working/retired. The category for peer social support is positive peer social support at 69% with the elderly receiving attachment social support and opportunity of nurturance at 88%, the category for loneliness level is low loneliness at 51% with low emotional loneliness and low social loneliness at 57% and 80%. The results of statistical tests (Chi- square) show that there is a relationship between social support from peers and the level of loneliness in the elderly with p value (0.022) < α (0.05). Conclusion: Peer social support is related to the level of loneliness in the elderly. Suggestion: It is recommended that all related parties increase promotive and preventive efforts in reducing loneliness inthe elderly by empowering peers. Keywords: elderly, loneliness, peer social support